Assessment of the severity and impact of drought spells on rainfed cereals in Morocco - Karrou M; Oweis, Theib Y. (Academic Journals, 2014)
Drought is a major factor affecting cereal production in most the rainfed areas of West Asia and North Africa. Recen increases in drought frequency in Morocco have resulted in the yields of field crops being extremely variable and generally low. The objective of this study is to assess drought severity in the main cereal production areas of Morocco and to evaluate its effects on grain yield. Also the study seeks to evaluate if the standarized precipitation index (SPI) may be used as a tool to predict drought and crop yield early in the season. Data analysis showed that for the period 1988 to 2008, yields fluctuated from 150 to 3000 kg/ha with a coefficient of variation of between 30 anf 50% in the north and 60 and 70% in the south. Based on the SPI, the regions studied experienced, on average, a drought once every 2.6 years. However, very severe droughts were observed only once in 7 years. The SPIs computed for the periods October to June and January to March were highly correlated. Moreover, there was a high positive correlation between the yield and the SPI calculated for the period January to March. The coefficients of determination varied between 0.28 and 0.69 for barley. It is concluded that soil moisture levels during the tillering and stem elongation periods of the cereals are the most important determinations of yield. Hence an SPI computed for the period January to March can be used to predict drought severity and yields early in the season.